What Does the LMC Look Like? It Depends on [M/H] and Age - Neige Frankel; Rene Andrae; Hans-Walter Rix; Joshua Povick; Vedant Chandra (The Astrophysical Journal)
We offer a new way to look at the LMC through stellar mono-abundance and mono-age mono-abundance maps. These maps are based on ≳500,000 member stars with estimates of [M/H] ( σ _[M/H] ~ 0.17) and age $({σ }_{{\rm{log}}τ }\unicode{x0007E}0.15$ ), derived from Gaia Data Release 3 XP spectra and photometry, which are tied to and validated against APOGEE. This results in the first area-complete, metallicity- and age-differentiated stellar maps of any disk galaxy. Azimuthally averaged, these maps reveal a surprisingly simple picture of the Milky Way's largest satellite galaxy. For any [M/H] below −0.1 dex, the LMC's radial profile is well described by a simple exponential, but with a scale length that steadily shrinks toward higher metallicities, from nearly 2.3 kpc at [M/H] = −1.8 to only 0.75 kpc at [M/H] = −0.25, as fit by forward modeling the spatial distribution of mono-[M/H] populations. The prominence of the bar decreases dramatically with [M/H], making it barely discernible at [M/H] ≲ −1.5. Yet, even for metal-rich populations, the bar has little impact on the azimuthally averaged profile of the mono-abundance components. Including ages, we find that the scale length is a greater function of age than of metallicity, with younger populations far more centrally concentrated. Only at old ages does the scale length change, specifically decrease, with increasing metallicity. These findings provide quantitative support for a scenario in which the LMC built its stellar structure effectively outside-in.